MarkSim standalone.V2 for DSSAT users - Jones, Peter G. (International Center for Tropical Agriculture, 2013)
Marksim_standalone.exe combined the basic routines from the original MarkSim version, produced at CIAT (International Center for Tropical Agriculture) and distributed on CD (Jones et.al., 2002), and the new MarkSimGCM web application (Jones et al. 2011a, b) that runs off Google Earth. The standalone version is designed for computer users that need to process a large amount of data. It eliminates their picking at a keyboard and abusing their eyesight by searching an on-screen map for the required data point. The original MarkSim_Standalone used six GCMs from the fourth approximation of the IPCC, the new one use 17 models from the CMIP5 range that were considered in the last IPCC report. It is designed to be used with DSSAT http://dssat.net/ and so it uses CLI files (see description below), existing, or constructed by the user, to create new CLI files and WTG files for the simulated weather data under a range of GCMs and Representative Concentration Pathways (RCP). The EXE runs from the DOS prompt (or a system program call). It will read a directory, work out a list of the CLI files in that directory, and create subdirectories for each CLI file. In each of these it will place up to 99 replicates of yearly weather data and a new CLI file describing the climate under the particular situation of GCM/scenario/year for which the user called.